2003
DOI: 10.1088/1009-9271/3/4/347
|View full text |Cite
|
Sign up to set email alerts
|

On the Spectral Index-Flux Density Relation for Large Samples of Radio Sources

Abstract: We present new statistical results on the spectral index-flux density relation for large samples of radio sources using archival data of the most sensitive surveys, such as 6C, Miyun, WENSS, B3, NVSS, GB87. Instrumental selection effects and the completeness of the catalogs are discussed. Based on the spectral indices calculated for about 200 000 sources from the WENSS (327 MHz) and NVSS (1.4 GHz) catalogs, we obtained (1) The median spectral index increases from α med ∼ −0.9 to α med ∼ −0.8 (S ν ∝ ν α), while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…frequencies. A similar flattening trend is also seen at both lower and higher frequencies, e.g., between 74 MHz and 1.4 GHz by Cohen et al (2004) and Tasse et al (2006), between 1.4 GHz and 325 MHz by de Vries et al (2002), between 325 MHz and 1.4 GHz by Zhang et al (2003) and Owen et al (2009), between 610 MHz and 1.4 GHz by Bondi et al (2007), and between 1.4 and 5 GHz by Prandoni et al (2006). Recently, Bornancini et al (2010) found that, for a nearcomplete sample of radio galaxies, there is no evidence for spectral steepening or flattening due to redshifted curved radio spectra.…”
Section: Spectral Indicessupporting
confidence: 69%
“…frequencies. A similar flattening trend is also seen at both lower and higher frequencies, e.g., between 74 MHz and 1.4 GHz by Cohen et al (2004) and Tasse et al (2006), between 1.4 GHz and 325 MHz by de Vries et al (2002), between 325 MHz and 1.4 GHz by Zhang et al (2003) and Owen et al (2009), between 610 MHz and 1.4 GHz by Bondi et al (2007), and between 1.4 and 5 GHz by Prandoni et al (2006). Recently, Bornancini et al (2010) found that, for a nearcomplete sample of radio galaxies, there is no evidence for spectral steepening or flattening due to redshifted curved radio spectra.…”
Section: Spectral Indicessupporting
confidence: 69%
“…The flux densities of point-like sources at λ6 cm were estimated from the extrapolation of the NVSS flux density at 1.4 GHz (Condon et al 1998) using a spectral index either taken from Vollmer et al (2005) or derived from the flux densities at 408 MHz and 1420 MHz from the Canadian Galactic Plane Survey (CGPS) (Taylor et al 2003). If no spectral index is available for a source, we adopted the mean value of α = −0.9 according to Zhang et al (2003) obtained from the NVSS and the WSRT source samples.…”
Section: Resultsmentioning
confidence: 99%
“…A flattening of the spectral index with lower flux density levels, as e.g. seen by Zhang et al (2003), was initially suspected by Windhorst et al (1993). A major line of argument is that, at sub-mJy levels, a change in population takes place: at mJy levels, the radio sky is completely dominated by AGN (see e.g.…”
Section: Spectral Index Vs Flux Densitymentioning
confidence: 93%